Emergy Comparison of Typical Coastal Urban Ecosystems in China - Fuqiang Qin; Lifang Wang; Shifen Shao (Complexity)
With outstanding geographical location and rich natural resources, coastal cities have become concentrated and active areas of human social and economic production. Furthermore, a large number of human activities have posed a great deal of ecological environmental pressure to coastal ecological areas. The emergy analysis method is selected to construct an index system with a total of nine indicators at five levels, including emergy source structure, social subsystem, economic subsystem, environmental subsystem, and comprehensive evaluation of sustainable development. The development level of subsystems and the sustainable development ability of ecosystem in Shenzhen, Dalian, Ningbo, Qingdao, and Xiamen were evaluated. The emergy sustainable index of the five cities is 0.10, 0.23, 0.31, 0.49, and 0.93, respectively. According to the evaluation results, coastal cities should comprehensively optimize the population structure, reasonably develop natural resources, make efficient use of marine resources, attach importance to the source control of pollutants, and strive to build a modern economy, so as to realize the sustainable development of coastal urban ecosystem.